Cefepime and Ceftazidime Safety in Hospitalized Infants. Issue 9 (September 2015) - Arnold, Christopher J.; Ericson, Jessica; Cho, Nathan; Tian, James; Wilson, Shelby; Chu, Vivian H.; Hornik, Christoph P.; Clark, Reese H.; Benjamin, Daniel K.; Smith, P. Brian
Abstract : Background: Cefepime and ceftazidime are cephalosporins used for the treatment of serious Gram-negative infections. These cephalosporins are used off-label in the setting of minimal safety data for young infants. Methods: We identified all infants discharged from 348 neonatal intensive care units managed by the Pediatrix Medical Group between 1997 and 2012 who were exposed to either cefepime or ceftazidime in the first 120 days of life. We reported clinical and laboratory adverse events occurring in infants exposed to cefepime or ceftazidime and used multivariable logistic regression to compare the odds of seizures and death between the 2 groups. Results: A total of 1761 infants received 13, 293 days of ceftazidime, and 594 infants received 4628 days of cefepime. Laboratory adverse events occurred more frequently on days of therapy with ceftazidime than with cefepime (373 vs. 341 per 1000 infant days, P < 0.001). Seizure was the most commonly observed clinical adverse event, occurring in 3% of ceftazidime-treated infants and 4% of cefepime-treated infants ( P = 0.52). Mortality was similar between the ceftazidime and cefepime groups (5% vs. 3%, P = 0.07). There was no difference in the adjusted odds of seizure [odds ratio (OR) = 0.96 (95% confidence interval: 0.89–1.03)] or the combined outcome of mortality or seizures [OR = 1.00 (0.96–1.04)] in infants exposed to ceftazidime versus those exposed to cefepime. Conclusions: In this cohort of infants, cefepime was associated with fewer laboratory adverse events than ceftazidime, although this may have been due to a significant difference in clinical exposures and severity of illness between the 2 groups. There was no difference in seizure risk or mortality between the 2 drugs.